Virtual exhibition: the porridges of Indonesia behind the delicacies / Amalia Lestari - Lestari, Amalia (Perpustakaan Tengku Anis (PTA), 2023)
Porridege is one famous type of dish in the world. With its smooth texture and simplicity, porridge holds a special bond with people around the world. Indonesia and other Asian countries are no strangers to the dish. With its history dating back hundreds of years ago through the Chinese who first introduced it, porridge or bubur in Indonesia developed into various kinds with different ingredients, tastes, and cultures behind it spread across the country.